The Correlation Between Physical Activity and Kidney Stone Formation: A Literature Review - Hernawan, Budi; Gonzales, Nico (Faculty of Medicine Universitas Sebelas Maret, 2023)
Background: Kidney stones or nephrolithiasis is a disease where crystals form in kidney due to increased excretion of stones-forming components such as calcium, oxalate, uric acid, cystine, xanthine, and phosphate, or reduced urine volume. In addition, poor eating and drinking habits along with lack of physical activity put individuals at a high risk of developing kidney stones. Previous studies showed that physical activity can both reduce and increase the risk of kidney stones.Purpose: This study aims to determine the relationship between physical activity and formation of kidney stones.Method: A literature review design was used by conducting a journal search through PubMed, Science Direct, and Google Scholar databases using the keywords (